Recent trends in alcohol outlet density, distances from educational institutions and sales campaigns in Chiang Mai municipality (Metropolitan), Thailand: Should we be worried for our youths? - Kanittha Thaikla (2018)
© The Author 2015. Medical Council on Alcohol and Oxford University Press. All rights reserved. Aims: Since 2008, alcohol control policies in Thailand have been considered quite comprehensive. The study aimed to investigate the subsequent changes in alcohol outlet density and patterns of sales promotion, which may be useful for monitoring the effectiveness of policies and helpful for planning prevention strategies to reduce alcohol-related harms. Methods: All accessible routes in the Chiang Mai Municipality (Metropolitan: CMM) were surveyed in 2009, 2011 and 2014. During each round of survey, the geographical coordinates of alcohol outlets and educational institutions in the CMM were recorded using the Global Navigation Satellite System (GNSS). In addition, alcohol sales campaigns were documented. Results: Three main trends emerged by 2014. The first was that alcohol outlet density had increased. Second, the average distances between alcohol outlets and educational institutions decreased with evidence of clustering near educational institutions. Lastly, increased advertising of alcohol promotions and new sales campaigns not previously seen in 2009 and 2011 promoted high volume drinking in Chiang Mai Municipality (CMM). Conclusion: Our study reflects the potential gaps between some of the intended consequences of alcohol control policies and the actural trends emerging in Chiang Mai, Thailand. Young people in CMM may be at a particularly high risk for alcohol-related problems due to high exposure to alcohol outlets and sales campaigns near their educational institution.